Dependence of the tidal deformability of neutron stars on the nuclear equation of state - Xie 谢, Wen-Jie 文杰; Chen 陈, Jian-Ling 建玲; Ma 马, Zi-Wei 紫微; Guo 郭, Jun-Hua 俊华; Zhu 祝, Long 龙 (Chinese physics C, 2023)
Within the Bayesian framework, using an explicitly isospin-dependent parametric equation of state (EOS) for the core of neutron stars (NSs), we studied how the NS EOS behaves when we confront it with the tidal deformabilities of canonical NSs with different error and different lower boundaries, and with the tidal deformabilities of massive NSs. We found that it does not significantly improve the constraints on the NS EOS but has a weak effect on narrowing down the slope parameter of the symmetry energy by decreasing the measurement errors of . Both the isospin-dependent and isospin-independent parts of the NS EOS were significantly constrained and raised as the tidal deformabilities of massive NSs were adopted in the calculations, especially in high-density regions. We also found that is more competent to limit the curvature parameter than the slope parameter of the symmetry energy, whereas the opposite occurs for the radius of canonical NSs . The tidal deformability of an NS with two times the solar mass is more sensitive to skewness than the curvature parameter of the symmetry energy, and and have no correlation with the former.